CHALLENGES IN THE LEGAL PROFESSION IN THE CONTEXT OF LEGAL SOCIOLOGY - Azizah Dzakiah Nurhakiki; Catharina Dewi Wulansari (CV. RADJA PUBLIKA, 2025)
The sociology of law is a discipline within sociology that experimentally and analytically examines the interdependent relationship between law and various social phenomena. It examines the function of law in society and how society influences and creates legal frameworks. It encompasses law as a regulatory system and a social phenomenon shaped by several social elements, including norms, values, culture, and social structures. As the study of the interaction between law and society, the sociology of law presents numerous challenges to the legal profession. These challenges include limited legal knowledge and understanding, the impact of social and cultural change, and technological developments. Furthermore, issues such as corruption, conflicts of interest, and lack of access to legal services also pose serious challenges to the legal profession.